PERTUMBUHAN, UMUR, DAN DIMORFISME SEKSUAL IKAN PELANGI ARFAK, Melanotaenia arfakensis Allen, 1990 DI SISTEM SUNGAI PRAFI, MANOKWARI, PAPUA BARAT - Emmanuel Manangkalangi; Simon P.O. Leatemia; Luky Sembel; Paskalina T. Lefaan; Ridwan Sala; M.F. Rahardjo (VOGELKOP: Jurnal Biologi, 2018)
ABSTRACTArfak rainbow fish, Melanotaenia arfakensis is an endemic fish on several river systems in the northeastern part of the Vogelkop peninsula. This study aims to describe the growth, age at first maturity, and sexual dimorphism of this endemic fish on the Nimbai Stream and the Aimasi Stream, the Prafi River system. The fish were caught using handnet, then were measured their standard length and individual weight. Data were analyzed to estimated growth patterns, von Bertalanffy's growth rate, age at first maturity and sexual dimorphism characteristics. The results showed that male growth patterns varied, with a tendency of the increase in body length faster than that of body weight (negative allometric patterns) with b values ranging from 2.886 to 3.132. On the other hand, the female individuals had positive allometric patterns (b values ranged from 3.062 to 3.378). The growth rate (K) of male body length was faster (0.165-0.174) than that of female individuals (0.159-0.163). Male individuals reached the first maturity condition earlier (at age of 1.83-2.18 years) than female individuals (at age of 2.49-2.64 years). Sexual characteristics between the sexes are related to body height starting to appear when fish are of a standard length of larger than 18.22 mm or when male fish begin to approach the time of the first sexual maturity. Understanding of growth, age, and the characteristics of the sexual dimorphism of endemic fish has an important meaning in monitoring population conditions and for conservation efforts in their natural habitat.